Access to infertility evaluation and treatment in two public fertility clinics and the reasons for withholding it: a prospective survey cohort study of healthcare professionals. Issue 12 (12th December 2020) - Elenis, Evangelia; Skoog Svanberg, Agneta; Leandersson, Pia; Lind, Judith; Sydsjö, Gunilla
Abstract : Objectives: Study the proportion of patients affected by involuntary childlessness who are denied fertility treatment and the reasons behind this in a publicly funded healthcare system. Design: Survey study using prospectively collected information by healthcare professionals. Setting: Two university-affiliated fertility clinics in Sweden. Participants: Single women and couples in heterosexual and homosexual relationships seeking fertility evaluation and treatment between November 2017 and April 2018 (943 individual cases). Primary and secondary outcome measures: Number and proportion of individuals who were either denied, delayed or granted fertility treatment directly. Furthermore, the reasons behind delaying or completely withholding treatment. Results: The majority of those seeking evaluation were heterosexual couples (75%), while 14% were single women and 7.5% were same-sex couples. The great majority of those undergoing evaluation were granted treatment either directly (85%) or after in-depth evaluation (7.5%), while 7.5% were denied treatment. Among those who were denied treatment, there were a greater proportion of single women and couples seeking treatment with donated gametes. Among heterosexual couples, gamete origin was not associated with treatment refusal. Although age did not differ between those granted and denied treatment, a higher body mass index (in both recipient and partner, when applicable) was observed among those being refused treatment. Fertility specialists in Sweden focused their assessment on parental factors that may indirectly entail a risk of harm to the future child, such as medical and psychiatric conditions of the individuals involved, their financial constraints and other social reasons, substance abuse and female obesity. Conclusion: Being single or receiving treatment with donated gametes can both be reasons for withholding fertility treatment. Although difficult to operationalise, parenting assessment in Sweden is employed interchangeably in treatments with donated gametes (legally mandated assessment) and even autologous gametes (non-legally mandated assessment)—making evident a need for clear official policy guidelines regulating these assessments and the provision of treatment.